Unusual clinicoradiographic presentation of a lateral periodontal cyst. - H T Kumuda Arvind Rao; S Ram Shetty; S Babu (Tehran University of Medical Sciences, 2012)
The lateral periodontal cyst is an uncommon, but well-recognized type of developmental odontogenic cyst. Lateral periodontal cysts are defined as non-keratinized and non-inflammatory developmental cysts located adjacent or lateral to the root of a vital tooth. It is a relatively uncommon lesion found mostly in adults (5th to 7th decades) and it is rare in young people under 30 years of age. A common site of occurrence is the mandibular premolar region. It does not have a predilection for any race or sex. Histopathologically, the lateral periodontal cyst lining is characterized by a thin cuboidal to stratified squamous non-keratinizing epithelium, ranging from one to five cell layers and presence of one or more epithelial thickenings or plaques.The purpose of this article is to report a case of interradicular radiolucent cystic lesion in a thirteen-year-old girl, located in a rare site of the maxillary premolar area, mimicking clinical and radiographical features of a residual cyst, but histopathologically proven to be a lateral periodontal cyst.